Comprehensive Analysis of Drinking Water Readily Accessible in Bangladesh (Journal of Bio-Science, 2026)
The study was conducted to assess and generate information on the quality of bottled and jarred drinking water available in the markets of Bangladesh, analyzing 35 branded bottled water and 250 jarred water samples from 18 districts. Parameters examined included total dissolved solids, chloride, nitrite, nitrate, lead, chromium, iron, pH, and microbial content (total and fecal coliform). The samples were analyzed in triplicate at accredited laboratories. Bottled water TDS (total dissolved solids) levels ranged from 8 to 240 mg/L, well below the Bangladesh standard of 500 mg/L, likely due to reverse osmosis technology reducing mineral content. TDS levels in jarred water ranged from 62 to 474 mg/L, with 11% of samples exceeding 300 mg/L. Although these higher levels were observed, they remain within acceptable limits for safe consumption. Chloride concentrations were acceptable, ranging from 1.97 to 55 mg/L for bottled water and 3.99 to 91.97 mg/L for jarred water. Other chemical parameters (NO2, NO3, Pb, Cr, and Fe) were undetectable. pH values of both bottled (6.36 to 7.70) and jarred (6.73 to 7.75) were within the safe range of 6.4 to 7.4. Microbial analysis revealed that bottled water was almost free of contamination (